Intellectual Capital and Financial Performance in Small Manufacturing Companies: The Moderating Effect of Managerial Ambidexterity - Ortiz Regalado, Oscar (Pontificia Universidad Católica del Perú, 2024)
Intellectual capital is crucial for the development and sustainable success of small manufacturing enterprises in emerging economies, and it has gained considerable relevance in business management. Despite numerous studies on intellectual capital and financial performance, several questions remain unresolved, such as: What is the relationship between intellectual capital and financial performance in small businesses? and What effect does managerial ambidexterity have on the relationship between intellectual capital and financial performance in small businesses? These questions highlight the need to address existing knowledge gaps. This study determined the relationship of intellectual capital as a whole, as well as each of its dimensions, with the financial performance of small businesses. Additionally, it examined the moderating effect of managerial ambidexterity on the relationship between intellectual capital, both as a whole and in each of its dimensions, and the financial performance of small businesses. The research adopted a quantitative and cross- sectional approach, involving 506 owner-managers. The questionnaire used consisted of 46 questions, and the collected data were subjected to Cronbach's Alpha tests and an Exploratory Factor Analysis. Finally, the validity of the proposed model was verified through a Confirmatory Factor Analysis and Structural Equation Modeling, using SPSS 27 and AMOS 24. The results indicate that intellectual capital, composed of human, structural, and relational capital, has a positive and significant relationship with financial performance. Furthermore, managerial ambidexterity was found to positively moderate this relationship, enhancing financial performance through the balance of exploitation and exploration activities. However, no significant moderating effect of ambidexterity was found on the relationship between human capital and financial performance.

El capital intelectual es crucial para el desarrollo y éxito sostenible de las pequeñas empresas manufactureras en economías emergentes y ha tomado una relevancia considerable en la gestión empresarial. Aunque existen numerosas investigaciones sobre el capital intelectual y el desempeño financiero, persisten preguntas sin resolver, tales como: ¿Cuál es la relación entre el capital intelectual y el desempeño financiero en las pequeñas empresas? y ¿Qué efecto tiene la ambidestreza del gerente en la relación entre el capital intelectual y el desempeño financiero en pequeñas empresas? Estas preguntas subrayan la necesidad de abordar las brechas de conocimiento existentes. El presente estudio determinó la relación del capital intelectual en su totalidad, así como de cada una de sus dimensiones, con el desempeño financiero de las pequeñas empresas. Además, se examinó el efecto moderador de la ambidestreza del gerente en la relación entre el capital intelectual, tanto en su conjunto como en cada una de sus dimensiones, y el desempeño financiero en las pequeñas empresas. La investigación adoptó un enfoque cuantitativo y transversal, en el cual participaron 506 gerentes-propietarios. El cuestionario utilizado constó de 46 preguntas, y los datos recolectados fueron sometidos a pruebas de Alfa de Cronbach y a un Análisis Factorial Exploratorio. Finalmente, se verificó la validez del modelo propuesto mediante un Análisis Factorial Confirmatorio y Modelado de Ecuaciones Estructurales, utilizando SPSS 27 y AMOS 24. Los resultados indican que el capital intelectual, compuesto por capital humano, estructural y relacional, tiene una relación positiva y significativa con el desempeño financiero. Además, se encontró que la ambidestreza gerencial modera positivamente esta relación, mejorando el desempeño financiero a través del equilibrio de actividades de explotación y exploración. No obstante, no se halló un efecto moderador significativo de la ambidestreza en la relación entre el capital humano y el desempeño financiero.
Keywords: Calidad total; Manufacturas--Perú; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04